Use of Near-infrared Spectroscopy and Implantable Doppler for Postoperative Monitoring of Free Tissue Transfer for Breast Reconstruction: A Systematic Review and Meta-analysis. Issue 10 (October 2019) - Berthelot, Melissa; Ashcroft, James; Boshier, Piers; Hunter, Judith; Henry, Francis Patrick; Lo, Benny; Yang, Guang-Zhong; Leff, Daniel
Abstract : Background: Failure to accurately assess the perfusion of free tissue transfer (FTT) in the early postoperative period may contribute to failure, which is a source of major patient morbidity and healthcare costs. This systematic review and meta-analysis aim to evaluate and appraise current evidence for the use of near-infrared spectroscopy (NIRS) and/or implantable Doppler (ID) devices compared with conventional clinical assessment (CCA) for postoperative monitoring of FTT in reconstructive breast surgery. Methods: A systematic literature search was performed in accordance with the preferred reporting items for systematic reviews guidelines. Studies in human subjects published within the last decade relevant to the review question were identified. Meta-analysis using random-effects models of FTT failure rate and STARD scoring was then performed on the retrieved publications. Results: Nineteen studies met the inclusions criteria. For NIRS and ID, the mean sensitivity for the detection of FTT failure is 99.36% and 100% respectively, with average specificity of 99.36% and 97.63%, respectively. From studies with sufficient reported data, meta-analysis results demonstrated that both NIRS [OR = 0.09 (0.02–0.36); P < 0.001] and ID [OR = 0.39 (0.27–0.95); P = 0.04] were associated with significant reduction of FTT failure rates compared with CCA. Conclusions: The use of ID and NIRS provided equivalent outcomes in detecting FTT failure and were superior to CCA. The ability to acquire continuous objective physiological data regarding tissue perfusion is a perceived advantage of these techniques. Reduced clinical staff workload and minimized hospital costs are also perceived as positive consequences of their use. Abstract : Supplemental Digital Content is available in the text.